2020
DOI: 10.1111/dmcn.14489
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of cognitive development in children with neurofibromatosis type 1 and plexiform neurofibromas

Abstract: Aim To describe the cognitive development of children with neurofibromatosis type 1 (NF1) and plexiform neurofibromas, and identify predictors of cognitive development. Method Participants included 88 children with NF1 and plexiform neurofibromas (50 males, 38 females, aged 6–18y, mean=12y, SD=3y 7mo) on a natural history study at the National Cancer Institute. Neuropsychological assessments (e.g. IQ, academic achievement, attention, and executive functioning) were administered three times over 6 years. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…A significant finding in this study, both for the NF1 and control groups, was the impact of maternal education on cognitive and behavioural development. In a longitudinal study of cognitive development in children aged 6-18 years with NF1, Hou et al (2020) found that higher parental education related to higher IQ, Maths, reading and cognitive scores (Hou et al, 2020). Two recent studies have also examined the cognitive and academic differences in children with inherited versus de novo NF1 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…A significant finding in this study, both for the NF1 and control groups, was the impact of maternal education on cognitive and behavioural development. In a longitudinal study of cognitive development in children aged 6-18 years with NF1, Hou et al (2020) found that higher parental education related to higher IQ, Maths, reading and cognitive scores (Hou et al, 2020). Two recent studies have also examined the cognitive and academic differences in children with inherited versus de novo NF1 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Further research will be necessary, especially to precisely assess the heritability of IQ in both sporadic and familial NF individuals. 32 Additional factors influencing cognitive development in children with NF1 like cerebral lesions in MRI 33 or clinical features like plexiform neurofibromas 34 needs to be taken into consideration as well.…”
Section: Discussionmentioning
confidence: 99%
“…Ortopedske komplikacije se rešavaju fizikalnom, korektivnom gimnastikom ili, u najtežim slučajevima, zahtevaju hirurško lečenje [2] . Potrebna je sveobuhvatna neuropsihološka procena za decu sa NF 1 [43] . Kognitivni poremećaji, pridruženi ADHD i teškoće u učenju zahtevaju rane i redovne konsultacije dečijeg psihijatra, psihologa i logopeda.…”
Section: Dijagnostika I Lečenjeunclassified